2010
DOI: 10.1128/jvi.00560-09
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Wasting Disease (CWD) Susceptibility of Several North American Rodents That Are Sympatric with Cervid CWD Epidemics

Abstract: Chronic wasting disease (CWD) is a highly contagious always fatal neurodegenerative disease that is currently known to naturally infect only species of the deer family, Cervidae. CWD epidemics are occurring in free-ranging cervids at several locations in North America, and other wildlife species are certainly being exposed to infectious material. To assess the potential for transmission, we intracerebrally inoculated four species of epidemic-sympatric rodents with CWD. Transmission was efficient in all species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 28 publications
2
51
0
Order By: Relevance
“…Heisey et al (14) previously reported a median survival time of 270 dpi for M. pennsylvanicus i.c. challenged with CWD-positive Wisconsin white-tailed deer brain homogenate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heisey et al (14) previously reported a median survival time of 270 dpi for M. pennsylvanicus i.c. challenged with CWD-positive Wisconsin white-tailed deer brain homogenate.…”
Section: Discussionmentioning
confidence: 99%
“…Heisey et al (14) have since shown that other vole and Peromyscus species are indeed susceptible to intracerebral (i.c.) inoculation with CWD.…”
mentioning
confidence: 99%
“…[22][23][24] However, intracerebral CWD inoculation caused prion infection in voles, hamsters, ferrets, sheep, cats, mink, and cattle, with variable attack rates. [25][26][27][28][29][30][31][32][33] Wild type mice and raccoons resisted CWD prion infection (Table 1). 16,34,35 An extensive study of CWD susceptibility in transgenic mice expressing ovine and bovine PrP C revealed no mice with prion disease, supporting the strong barrier to CWD infection observed in sheep and cattle.…”
Section: Cross-species Cwd Prion Transmissionmentioning
confidence: 99%
“…Rodents have been hypothesized to be potential reservoirs of TSEs (Heisey et al 2010). Therefore, we specifically extended the PRNP and PRND data sets for diverse rodent species.…”
Section: Discussionmentioning
confidence: 99%